2021
DOI: 10.1038/s41598-021-88392-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of gravitational effects on mouse skeletal muscles under microgravity and artificial 1 g onboard environment

Abstract: Spaceflight causes a decrease in skeletal muscle mass and strength. We set two murine experimental groups in orbit for 35 days aboard the International Space Station, under artificial earth-gravity (artificial 1 g; AG) and microgravity (μg; MG), to investigate whether artificial 1 g exposure prevents muscle atrophy at the molecular level. Our main findings indicated that AG onboard environment prevented changes under microgravity in soleus muscle not only in muscle mass and fiber type composition but also in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…Mammals (i.e., humans and rodents) have evolved with the never-ending downward pull of gravity on Earth, and therefore postural muscles such as the soleus are known to be most affected with spaceflight. Similar to unloading models on Earth, spaceflight and microgravity exposure in rodents unloads the postural soleus causing extensive muscle atrophy and a fiber-type shift from slow-oxidative to fast-glycolytic [ 4 , 5 , 6 , 7 , 8 , 9 ]. Similar changes have also been observed in human soleus muscles after 17 days of spaceflight [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mammals (i.e., humans and rodents) have evolved with the never-ending downward pull of gravity on Earth, and therefore postural muscles such as the soleus are known to be most affected with spaceflight. Similar to unloading models on Earth, spaceflight and microgravity exposure in rodents unloads the postural soleus causing extensive muscle atrophy and a fiber-type shift from slow-oxidative to fast-glycolytic [ 4 , 5 , 6 , 7 , 8 , 9 ]. Similar changes have also been observed in human soleus muscles after 17 days of spaceflight [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle tissue alterations such as atrophy, muscle force decrease, and shift in muscle fiber composition occur during aging, pathology onset, radiation exposure, and mechanical unloading. A fast deterioration of skeletal muscle tissue, in particular, affects astronauts who are exposed both to gravitational unloading (hereafter termed microgravity or “μ g ”) and to cosmic radiation during spaceflight. For this reason, a variety of strategies for muscular maintenance in vitro and in vivo has also been devised for terrestrial benefit, including physical exercise, mechanical stimulation in the form of vibrations and pressure application, electrical stimulation, exposure to hypergravity, administration of soluble factors (such as activin type IIB receptor, recombinant myokine irisin, and myostatin antibody YN41), and even genetic transduction finalized to the overexpression of nucleic acids (such as a long noncoding RNA termed lncMUMA) . A common approach against skeletal muscle waste due to mechanical unloading also consists of the supply of antioxidant compounds, like for instance (-)-epicatechin, lecithin, N -acetylcysteine, complex mixtures of polyphenols associated with other antioxidants (such as vitamin E, selenium, and omega-3 fatty acids), or even seed extracts (from Oenothera odorata) .…”
Section: Introductionmentioning
confidence: 99%
“…4 ). Therefore, while we identified regulation of mitochondrial function and lipid metabolism via DGE (see Additional file 5 ), as has been described previously in skeletal muscle following spaceflight [ 19 21 ], we characterized DAS as a novel means of modifying the transcriptome in response to microgravity. Further, we identified coordinate changes in splicing and microgravity-induced physiological adaptations of hind limb muscle, which included muscle atrophy (see Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Most interest has been paid to the transcriptomic effects at the level of differential gene expression (DGE). Recent transcriptome analyses of skeletal muscle in mice [ 19 21 ] have annotated microgravity-induced DGE of gene networks related to contractile machinery, calcium homeostasis, muscle development, cellular metabolism, inflammatory/oxidative stress response, and mitochondrial function. One landmark study, the National Aeronautics and Space Administration (NASA) Twins Study [ 22 ], identified DGE between monozygotic twins that were exposed to spaceflight or ground control conditions for one year.…”
Section: Introductionmentioning
confidence: 99%